Assessing lake vulnerability to climate change using the coupled MIKE SHE/MIKE 11 model: Case study of Lake Zazari in Greece. Paper presented at 11th World Congress on Water Resources and Environment (EWRA 2019) “Managing Water Resources for a Sustainable Future”. Madrid, Spain, 25-29 June 2019 - Demertzi, Κ.; D. Papamichail; Papadimos, D. (2019)
If the worst predictions of general circulation models (GCMs) about climate change become true, then lakes will hardly manage to maintain their current conditions (Zhang et al. 2016) especially in regions, which have been identified as climate change hot spots such as the countries of Mediterranean Basin (Loizidou et al. 2016) from which Greece is of special interest since it has 54 lakes/reservoirs of 0.5 km2 minimum size. The hydrological models are important tools for assessing the water balance components of lakes and for supporting the design of water management strategies. Depending on the modelling purposes and the specific attributes of a lake, different types of models and different levels of model complexities can be selected, starting from complex models such as MIKE SHE (Abbott et al. 1986), WATLAC (Zhang 2011) or using simpler methods (Yang et al. 2018). The MIKE model is among the most integrated models and has been used in the past for similar cases (Singh et al. 2010), while in combination with the future climate projections of general circulation models (GCMs), can be used to investigate lake conditions under future climate scenarios. The aim of this study is to present an application for analyzing the vulnerability of a lake to climate change using the MIKE SHE/11 model using as a case study the Lake Zazari in Greece.